PENGUATAN KELEMBAGAAN KELOMPOK TANI PADI SAWAH DAN DAMPAKNYA PADA PENERAPAN SISTEM TANAM LEGOWO - Yunita P. Djamil; Asda Rauf; Yuriko Boekoesoe (Agrinesia: Jurnal Ilmiah Agribisnis, 2016)
This study aims to determine the factors that influence the management of farmers groups in the application of cropping systems in the district legowo Kabila Bone Bolango District. And to determine the impact of the adoption of cropping systems to farmers in the district legowo Kabila Bone Bolango District. This research was conducted in December to February, 2016. The method used was survey method. Data collected included primary and secondary data. The samples of farmers using the method slovin, so the sample size is 53 farmers. The analysis is SWOT analysis, and Revenue Analysis. The results showed that the factors that affect the management of farmers groups: (1) Strategy (SO): The existence of government policies in providing facilities and infrastructure that support the farmer group Strategy (WO): The existence of effort and attention from the government or the extension to be informed or fostering the farmer groups. Strategy (ST): The farmer group needs the support of government in smoothing delays seeds / inputs to support the success of farming. Strategy (WT): Need for counseling or mentoring farmer groups so that mastery of technology is still lacking that have an impact on technological limitations will not affect farming. (2) The impact of the adoption of cropping systems legowo to farmers, namely on increasing farmers' income, with total revenues of Rp. 6,595,928.94 / farmer, or Rp. 10,690,649 / Ha. Keywords: Institutional strengthening farmer groups, The system legowo, farmers' income